Students’ experiences of placements in urban Indigenous health contexts: developing a culturally responsive workforce - Kate Odgers-Jewell; Alison Nelson; Renee Brown; Nicole Hunter; Tiffany Atkins; Kelly Menzel (BMC Medical Education)
Abstract Background A culturally responsive health workforce is essential to ensure the delivery of culturally safe health services that meet Aboriginal and Torres Strait Islander Peoples needs. In partnership with universities, placement providers play an essential role in creating opportunities for immersive experiences that enable students to develop their cultural responsiveness. This study evaluated students’ experiences of an innovative student placement model embedded within an urban Aboriginal and Torres Strait Islander Community-Controlled Health Organisation. Methods Students completed pre and post placement surveys administered using a web-based interface. The surveys involved five-point Likert and open-ended response items exploring students’ perceptions of their knowledge, skills development, awareness and self-development, and overall placement experience. Frequencies were calculated for the variables of interest and compared between pre and post surveys. The sign test for matched pairs was used to calculate differences between pre and post surveys, and a one-sided hypothesis test was utilised to determine if the level of agreement increased from pre to post survey. Qualitative data obtained for seven questions were thematically analysed using Groundwater Method, an Indigenous data analysis technique. Results Between January 1, 2017, and June 30, 2019, 938 students from 32 disciplines were placed within the organisation and its Member services. Survey responses were received from 338 participants pre-placement, and 158 participants post-placement. The matched pre-post group contained 81 students. The results indicate significant positive changes in cultural responsiveness, skills development, awareness, and self-development when comparing pre- and post-placement responses. Students’ overall satisfaction with the quality of their placement was positively associated with their intention to work in Aboriginal and Torres Strait Islander health contexts in the future. Key pre-placement themes included competence, cultural skills, support and fear, and key post-placement themes included expertise, cultural responsiveness, learning environment and challenges. Conclusions Indigenous-led, regionally coordinated placements in urban Indigenous health contexts can support transformative learning and the development of a culturally responsive workforce. Universities should aim to develop reciprocal relationships with Indigenous-led organisations to support students to develop their cultural responsiveness and improve the provision of culturally safe care for Aboriginal and Torres Strait Islander Peoples. Future research should explore the longer-term impacts of student placements on cultural responsiveness, attitudes, values, and behaviours, as well as the experiences of Aboriginal and Torres Strait Islander Peoples interfacing with university students on placement in urban settings. Note We will predominantly use the term ‘Aboriginal and Torres Strait Islander Peoples’, as opposed to ‘Indigenous’ or ‘First Nations’. When the term ‘Indigenous’ is used, it largely relates to government policy - except when referring to Indigenisation of curriculum and Indigenous Knowledges - and where ‘First Nations’ is used, it is in a global context. In addition, we use the term ‘Peoples’ to signify that Aboriginal and Torres Strait Islander Peoples are not one People or Nation, but a collective of Peoples and Nations.